Does money matter, and for whom: the importance of financial motivational factors among employees of banks in Poland - Markiewicz, Magdalena; Leśniak, Renata; Sokołowska, Katarzyna (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The organisation’s approach to building human capital is an essential factor in the success of market entities, and it determines a competitive advantage in the market. Due to the challenges and various market changes that banks face, building an effectively motivated multigenerational employee team and understanding employee intrinsic and extrinsic motivation is very important. Aim: The paper aims to contribute to the literature and fill the research gap on the financial motivators available in banking and non-banking entities. The paper examines the role and importance of financial incentives, regularly used in the banking sector, in conjunction with a comprehensive analysis of their significance for representatives of different generations (X, Y, Z), gender, and career level in the sample of various institutions in the banking sector in Poland. Results: The paper outlines the opportunity to revise incentive systems in banking operations. The analysis was made twofold: firstly, within extensive desk research, and secondly, based on the empirical survey in the form of an individual research questionnaire carried out among 418 employees of various banks and companies from their capital groups just before the pandemic in 2020. The results were examined using statistical analysis, including non-parametric tests. We identified multiple respondents’ attitudes to motivational financial factors and classified their importance concerning generation, age, and organisational position. The study’s results indicate that generational and gender differences affect the perception of bank financial incentive tools. Some financial motivational factors regularly used in banks do not equally motivate employees, which leads to the conclusion that banking institutions should inevitably include generational and gender factors in their motivational approach to employees.